REPRESENTASI REMAJA DALAM FILM INDONESIA (The Commercium, 2023)
Youth films are a social phenomenon that plays a major role in the process of forming cultural ideas related to the world of youth. The study of youth films is not simple because there is a tendency to present youth in different ways depending on the social context in the time period when the film is produced. This research is a descriptive qualitative research using a constructivist paradigm. Data collection techniques used observation, documentation, and literature study by observing primary data sources in the form of KKn di Desa Penari, Qorin, Dear Nathan: Thank You Salma, 12 Cerita Glen Anggara, Kukira Kau Rumah, and Like & Share, as well as data sources secondary data obtained from various literature or literature studies. By using the genre analysis method by Jane Stokes, the research on the six films shows that there are forms of youth representation, namely: (1) Representation of adolescents who are full of emotional turmoil in setting conventions, (2) Representation of youth hanging out culture in location conventions, (3) Representation of be yourself principles on self-actualization of adolescents in iconographic conventions, (4) Representation of assertive behavior of adolescents in character conventions, (5) Representation of adolescents' awareness of sexual violence and mental health emergencies in conventions of narrative events, and (6) Representation of adolescents far from their parents in conventions of structural plot. Thus, some differences or shifts were found in showing youth in youth films in each decade.